PEMANFAATAN INFUSA DAUN SIRIH MERAH (Piper crocatum) SEBAGAI ANTI-OBESITAS PADA MENCIT (Mus musculus) - Desty Apritya; Miarsono Sigit; Retina Yunani; Fuji Lestari (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
The purpose of this research is to know the effectiveness of red betel leaf infusion (Piper crocatum) as anti-obesity in mice (Mus musculus). Other parameters of this study to know the relationship between changes in blood glucose levels to obesity in experimental animals. Experimental animals used were 24 male mice. The design of this research is completely randomized design (CRD) with 4 treatments 6 repetitions. There are four treatmens P0 (Control), P1 (6 mice by giving a betel leaf infusion with a concentration of 5%), P2 (6 mice by giving a betel leaf infusion with a concentration of 10%), and P3 (6 mice by giving a betel leaf infusion with a concentration of red 15%). The treatment is carried out once every day for 21 days. Before treatment, initial weight was weighed and blood glucose level examination continued on the 7th day, on the 14th day, and on the 21st day. Data obtained from the results of weighing and checking blood sugar levels were further analyzed using the ANOVA test which statistically showed no significant changes (P> 0.05) of body weight and blood glucose levels in mice (Mus musculus) given infusion red betel leaf (Piper crocatum).